(untitled) - Gere, James M. (Victoria, Australia, 2004)
This engineering textbook introduces mathematical techniques and the physical properties of common materials for analyzing the mechanical behavior of bars with axial loads, shafts in torsion, beams in bending, and columns in compression. The sixth edition adds two sections on singularity functions. The CD-ROM contains six tutorials.
Keywords: Strength of materials,Materials; Problems, exercises, etc.,Problems, exercises, etc